Les défis de la mobilisation collective et de l’organisation politique des travailleurs de plateformes au Brésil : une approche ergologique. - Christo, Cirlene; OLIVEIRA, Simone; ALVAREZ, Denise; MASSON, Letícia; LACOMBLEZ, Marianne (Industrial Relations / Relations Industrielles, 2023)
Given the specificities of the phenomenon of labor platformization in a country that occupies a position of dependence within the capitalist system, the objective of this article is to identify the alternative forms and dynamics of political organization and collective mobilization adopted by platform drivers and delivery workers in Brazil. The path chosen in the study reported here required not only an analysis of the national social context, in interaction with neoliberal rationality, but also an analysis of the literature evoking the difficulties of union organization among precarious workers. The analysis focused on current experiments, which are part of a search for alternative forms of collective organization for platform workers to traditional unionization. From a theoretical-methodological standpoint, the ergological perspective adopts an integrated approach at the macro and institutional levels and at the micro level of the collective dynamics of workers in their daily struggles. Involved in this research were the leaders, animators and members of two associations, two collectives opting for self-management and a network of self-organizing workers. The options and obstacles encountered in building organization and joint action were identified. We found that the cohesive strength of the collective entities analysed was based in the sharing of values that support the course of joint action. Thus, in the face of the heterogeneity of these groups of platform workers, and by adopting a less restrictive conception of what is covered by a professional or economic category, we raise the possibility of the formation of alternative movements and organizational forms that could prove to be conducive to their interests.